Crescimento radical, de parte aérea e componentes do rendimento de híbridos de canola convencionais e tolerantes à herbicidas em ambientes contrastantes - Mattioni, Tania Carla (2015)
Canola (Brassica napus L. var. olerifera) is presented as an alternative for winter cultivation in southern Brazil. The objective of this study was to characterize the shoot growth, root system and components yield of canola hybrids. The experiment was conducted at two locations: Passo Fundo - RS and Guarapuava - PR, using a randomized block design with four replications. The hybrids were Hyola 61, Hyola 571CL, K 10050, 92002 and H Hyola 751TT. Measured shoots variables were: height, leaf number, unit and total leaf area, leaf area index, shoots dry mass and number of branches. To evaluate the root system was collected soil monolith and used for image analysis measuring length, surface area and the total volume and root diameter classes, the root density and specific surface area. The shoot assessments and root system were applied on plants contained in the half meter, enabling the conversion hectare. To yield components and the number of branches in ten plants was used by measuring the number of pods branches, seed yield and thousand grain weight. The hybrid K 10050 had the highest development of shoot, root system, as well as increased productivity. The hybrids have the greatest concentration of fine intermediate roots with a diameter between 1 and 5 mm thick. Is a strong correlation between volume root number of leaves and root MS and MS shoot.